Stop Bullying, Bangun Empati Psikoedukasi Pencegahan Kekerasan dan Dukungan Kesehatan Mental bagi Komunitas SMK TechnoMedia - Ismanto, Juli (Abdimisi, 2025)
Bullying is a phenomenon that causes psychological and social harm to students, affecting their mental health, social interactions, and academic performance. The Community Service Activity (PKM) with the theme “Stop Bullying, Build Empathy: Psychoeducation on Violence Prevention and Mental Health Support for the SMKTechnoMedia Community” aims to raise awareness and develop effective preventive strategies within the school environment. Through psychoeducation, interactive training, and group discussions, the program successfully improved students' and educators' understanding of bullying definitions, types, and impacts. Activity outcomes showed changes in participants' attitudes, including increased awareness in reporting bullying incidents and involvement in creating a more supportive environment. The implementation of strategies, such as the formation of an anti-bullying team, counseling support, and strengthening school policies, has had a positive impact in creating a safer educational ecosystem. Despite challenges in implementing prevention measures, such as resistance to cultural change and insufficient training for educators, the program demonstrates that empathy-based and psychoeducational interventions can be effective solutions. To ensure the sustainability of the program, continuous monitoring, collaboration with psychologists, and broader outreach are needed. With a systematic strategy, it is hoped that the SMKTechnoMedia community can create an educational environment free from bullying and supportive of students' mental well-being. Keywords: Bullying; Empathy;Mental Health, Violence Prevention; Psychoeducation.